Boundary element methods in applied mechanics : proceedings of the First Joint Japan/US Symposium on Boundary Element Methods, University of Tokyo, Tokyo, Japan, 3-6 October 1988 - Tanaka, M. (Masataka), 1943-; Cruse, Thomas A. (Pergamon Press, 1988)
This Proceedings features a broad range of computational mechanics papers on both solid and fluid mechanics as well as electromagnetics, acoustics, heat transfer and other interdisciplinary problems. Topics covered include theoretical developments, numerical analysis, intelligent and adaptive solution strategies and practical applications.